The economic performance of hydropower dams supported by the World Bank Group, 1975-2015 - Saule Baurzhan; Glenn P. Jenkins; Godwin O. Olasehinde-Williams (Queen's University, Department of Economics, 2021)
This paper assesses the economic benefits of 57 World Bank Group-sponsored hydropower dam plant investments. Hydropower dams are among the main sources for producing electricity and the largest renewable source for power generation throughout the world. Hydropower dams are often a lower-cost option for power generation in Clean Energy Transition for addressing global climate change. Despite its conspicuous aspects, constructing hydropower dams has been controversial. Considering the World Bank's long history as the largest hydropower development financier, this study investigates its performance in supporting hydropower dams. The outcomes of this study apply to the wider hydropower development community. Of the projects in this study, 70% experienced a cost overrun, and more than 80% of projects experienced time overruns, incurring potential additional costs as a result. Despite the high cost and time overruns, this hydropower portfolio of dams produced a present value of net economic benefits by 2016 of over half a trillion USD. Based on our findings, the evaluated hydropower portfolio helped avoid over a billion tonnes of CO2 for an estimated global environmental benefit valued at nearly USD 350 billion. The projects' additional environmental benefits raise the real rate of return from 15.4% to 17.3%. The implication for hydropower developers is that the projects' assessment should consider cost and time overrun and factor them into the project-planning contingency scenarios. There is a considerable benefit for developing countries to exploit their hydropower resources if they can be developed according to industry practices and international standards. The case for developing hydropower may be stronger when considering its climate benefits. The net economic benefits of hydropower can be even higher if there is a greater effort to manage cost and time overruns.
Keywords: 330; investment appraisal; carbon emissions; cost overrun; hydropower; dams; World Bank